True heroes of sport - Fitzgerald, Donatella (Oxford University Press, 2010)
Some people in the world of sport are heroes only because they are the best at their sport. But the sportsmen and sportswomen in this book - Oscar Pistorius, Michael Phelps, Wilma Rudolph and Natalie du Toit - are all that and much more. All of them went through bad times and learned to be stronger people through sport. Because it isn't living through good times, but living through bad times that makes you into a true hero!